Country-specific participation patterns in transnational governance initiatives on sustainability: preliminary insights and research agenda - Tosun, Jale; Levario Saad, Emiliano; Glückler, Johannes; Irigoyen Rios, Alejandra; Lehmann, Rosa (Global challenges, 2023)
Transnational public-private governance initiatives (TGIs) have become key elements in global governance, especially in the governance of sustainability. Pertinent research has concentrated on why TGIs have emerged as well as on their impacts on political outcomes and questions related to their legitimacy. This instructive literature has predominantly focused on TGIs as entities in their own right. This explorative study contributes to the literature by advocating a complementary analytical perspective that pays attention to domestic-level patterns of participation in TGIs and national factors that determine which types of organizations (public, business, or civil society) participate in TGIs. It is shown for six Latin American countries (Argentina, Brazil, Chile, Colombia, Mexico, and Peru) that there exists cross-country variation in the composition patterns in 29 TGIs on sustainability, suggesting that national conditions matter for how organizations participate in them. By improving the knowledge of the national conditions, a more complete analysis of participation and the effectiveness of TGIs can be provided in global sustainability governance. In this spirit, in a last step, an agenda is developed for guiding future research on this topic.
Online veröffentlicht: 6. Juli 2023
Gesehen am 22.11.2023